RISK PROFILE IN YOUNG PATIENTS WITH ACUTE MYOCARDIAL INFARCTION: Risk Profile in Acute Myocardial Infraction - Fazal, Col Imran; Fazal, Col Imran; Safdar, Muhammad Hanif Khan; Ejaz, Amer; Awan, Zaheer Iqbal (Pakistan Armed Forces Medical Journal, 2010)
Objective: The objective of this study was to determine the frequency of risk factors in young patients with acute myocardial infarction and thus with ischemic heart disease (IHD), aged 20 to 40 years, in our population. Study Design: A descriptive study. Place and Duration of study: This Study was carried out at Combined Military Hospital, Kharian Cantonment Pakistan from January 2007 to December 2008. Patients and Methods: All patients who fulfilled the inclusion criteria who presented to emergency reception of the hospital with a diagnosis of Acute MI were included. The patients were admitted to coronary care unit (CCU) and were managed for Acute myocardial infarction (MI). Their detailed history was then taken including symptoms at presentation and their risk factors were assessed with the help of history and laboratory investigations. Results: A total of 137 patients were included during the study period. Mean age was 36 years (SD=3.67). Majority of patients were males. Smoking was the major risk factor (64.2%) followed by family history of IHD (30.7%). Conclusion: Most frequent risk factor for Acute myocardial infarction (MI) at young age is smoking followed by family history.